2021
DOI: 10.3390/su13105352
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID 19 Tourism: Will Digital Tourism Replace Mass Tourism?

Abstract: Recently, nations are struggling to mitigate the impact of the unprecedented COVID-19 outbreak on their economy. Many countries have imposed traveling restrictions to reduce people’s movement in order to avoid infection transmission. Traveling restrictions have jeopardized the tourism industry around the globe. If the situation persists, it will become challenging for the nations to open tourism. For this reason, the digitalization of tourism is a viable solution for this situation. However, it is essential to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 40 publications
1
72
0
3
Order By: Relevance
“…They can maintain the continuity of the tourism industry. They are useful for older people or with disabilities [37]. They can be described as consistent with the idea of SD.…”
Section: Recently Utilized Alternative Ways Of Mining Reclamationmentioning
confidence: 84%
See 1 more Smart Citation
“…They can maintain the continuity of the tourism industry. They are useful for older people or with disabilities [37]. They can be described as consistent with the idea of SD.…”
Section: Recently Utilized Alternative Ways Of Mining Reclamationmentioning
confidence: 84%
“…The latest experiences during the pandemic have drawn attention to digital solutions that allow visitors to contact tourist facilities remotely [37]. Examples include the provision of materials by the Coal Mining Museum in Zabrze in the form of short virtual walks [38].…”
Section: Recently Utilized Alternative Ways Of Mining Reclamationmentioning
confidence: 99%
“…These mental health conditions attack the HCWs due to many reasons like the nature of their work that require irregular and long duty hours, witnessing death and physical suffering of the patients in front of their eyes, uncertainty about definitive effective treatment for the patients. Also they are facing difficulties in balancing between their duty to help patients and their desire to protect themselves and their family members from infection which they may bring home [42,44]. This systematic review identified 12 studies that explored HCWs coping strategies during COVID-19 pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion of only empirical articles is due to the inclusion of statistically validated factors that determine GBE. This approach is used in the literature in the PRISMA method when applying SLR to areas, such as medicine [86,[94][95][96][97], management [88,98], consumer behavior [99], tourism [100], and others [81,85,90]. The SLR search of five databases yielded 3393 publications.…”
Section: Conducting the Slrmentioning
confidence: 99%